Comparison of Long-Term Outcomes in Real-World Patients Between Resolute Zotarilumus-Eluting and Paclitaxel-Eluting Stents in Small Vessel. (May 2016) - Kilickesmez, Kadriye Orta; Kocaş, Betül; Yildiz, Ahmet; Coskun, Ugur; Ersanli, Murat; Arat, Alev; Gürmen, Tevfik
Objective: To compare the long-term clinical outcomes between Resolute zotarolimus-eluting stent (R-ZES) and paclitaxel-eluting stent (PES) in patients with small coronary artery disease. Background: Patients with a small vessel diameter are independently associated with increased risk of adverse cardiac events after drug-eluting stent implantation. Methods: A cohort of 265 patients treated with R-ZES (185 patients with 211 lesions) or PES (80 patients with 100 lesions) in small vessel (≤2.5 mm) lesions were retrospectively analyzed. The primary end point of the study was the composite of major adverse cardiac events. The secondary end points included target lesion revascularization (TLR), target vessel revascularization (TVR), and stent thrombosis at 3 years. Results: The baseline characteristics were similar between the 2 groups. In the R-ZES group, the mean stent diameter was smaller and the total stent length per lesion was longer. Major adverse cardiac events occurred in 8 (10%) patients who had received PES and in 7 (3.8%) patients who had received R-ZES ( P = .07). The rates of 3-year TLR (2.2% vs 2.5%; P = 1.00) and TVR (5.4% vs 10.0%; P = .17) showed no statistically significant difference between the R-ZES and PES groups. The rate of stent thrombosis was 0.5% in the R-ZES group and 2.5% in the PES group ( P = .21). Conclusion: The rates of major adverse cardiac events and cardiac death were similar in the R-ZES-treated group compared with the PES-treated group.